kenman wrote:

If \(y = \frac {x^2 - y^2}{x-y}\) ( \(x \ne y\) ), then what is the value of \(y\) ?

1. \(x + y = 3\)

2. \(x - y = -3\)

(C) 2008 GMAT Club - m02#25

Hi All-

I'm struggling to see the logic behind the OA in this question. Taking the information from the question stem, we get y= (x+y)(x-y)/ (x-y), therefore y=x+y. Its easy to see that statement 1 is sufficient, but for statement 2, we will still get y=x+y because y=-3(x+y)/-3. We can pick a number of different values for x-y that equal -3 that fit the question stem (x is not equal to y). Can someone with better math skills than myself explain why statement 2 is sufficient? Cheers!

-Ken

Mark my words bro, if you follow the way you are solving the questions you will face a difficult time with DS questions.

Always simply the equations till end, else you will complicate the things for you... - GOLDEN RULE.

now when you got y =x+y => x must be 0

now when you will put x=0 in both the statements you will have unique value of Y.

=> both are sufficient.

Now spend at least 15-20 mins on the advice I gave you and try to put in every question. Always simplify and then go ahead.

_________________

Fight for your dreams :For all those who fear from Verbal- lets give it a fight

Money Saved is the Money Earned

Jo Bole So Nihaal , Sat Shri Akaal

Support GMAT Club by putting a GMAT Club badge on your blog/Facebook

GMAT Club Premium Membership - big benefits and savings

Gmat test review :

670-to-710-a-long-journey-without-destination-still-happy-141642.html